PARADIGMA HOLISME HEGELIAN DAN KRITIK ATAS LIBERALISME - Madung, Otto Gusti (Jurnal Ilmiah Peuradeun, 2014)
Liberal political ideology that promotes the democratization agenda and the implementation of human rights is seen as a normative goal of global political developments today. But liberalism does not actually escape from various critics. One radical criticism against liberalism derived from the communitarian camp that liberalism tends to privatize the concept of good life (religion, ideology) and put it in the private sphere. An important result or this is the lack of social solidarity. This paper tries to sharpen the criticism of the communitarian camp over liberalism with the knife of the Hegelian concept of holism. In liberal political theory, integralism or holism is criticized as the cause of totalitarian political systems. In this description will be shown that integralism or holism should not be contrary to the principles of individual rights. Holism or integralism suggests some fundamental criticisms of liberalism and proposes some solutions to overcome the problem of pathology of liberalism.